ANALISIS REALISASI BIAYA PADA KEGIATAN OVERBURDEN REMOVAL DI PT ABC KABUPATEN LAHAT PROVINSI SUMATERA SELATAN - M. Ikbal Aziz; Lina Rianti; Lendra Sagita Putri (Jurnal Cakrawala Ilmiah, 2023)
Mining sector is very closely related to mechanical device utilization and is inseparable from cost so that production targets can be achieved. Operational costs can affect the company’s income, so an analysis of operational costs is necessary. This study analyzed the realization of operational costs in fleet 1 overburden removal activities to determine lost opportunities experienced by a company. The analysis process was conductued by identifying the target and actual production of overburden fleet 1. The production target of overburden removal was 15,000 BCM with the tools used 1 digging equipment and 3 hauling equipment and the operational cost consisted of solar cost, oil cost, filter cost, grease cost, tire cost, repair/maintenance cost and operator salary cost. The total operational cost for overburden removal activity was Rp237,579,500 with the overburden transportation cost of Rp29,500 for a distance of 1.2 Km, the gross income carned was Rp435,309,080. The factors that caused the lost opportunity were the unachieved production factor of overburden removal fleet 1 which was Rp7,190,920 and the mechanical equipment maintenance factor which was Rp103,261,000 with a lost opportunity of Rp110,451,920.